Leituras de Weber e do Brasil: da política à religião, do atraso à modernidade - Carlos Eduardo Sell (Ciências Sociais Unisinos)
In the realm of Brazilian sociology two readings of Webers works have been historically prevalent, and each one had different repercussions on the diagnosis of the consolidation of modernity in Brazil. The first one, relying on Webers political sociology and his sociology of domination, has as its central authors Sergio Buarque de Holanda and Raymundo Faoro. The second one, more recent one, stresses Webers historical-comparative sociology of religions and is represented, among others, by authors such as Jessé Souza and Antonio Flávio Pierucci. The article describes these different readings of Weber and shows how different interpretations of the Brazilian reality are derived from them.